Strengthening Rembugan as A Mediation Model in The Resolution of River Water Pollution Disputes (A case study in Purbalingga, Central Java, Indonesia). - Nita Triana; Naqiyah Mukhtar; Farah Nuril Izza; Ade Tuti Turistiati (LAW REFORM, 2022)
Purbalingga as an industrial area is prone to pollution that has a detrimental impact on society and the environment. It is necessary to find a way that can bring together the parties involved to peacefully resolve environmental disputes. The purpose of this study is to strengthen rembugan as a mediation model for resolving pollution disputes in the old industrial area. This research is qualitative research with a socio-legal approach, by conceptualizing law as non-doctrinal. The results showed that rembugan is a community culture in dispute resolution that reflects the values of local wisdom possessed by the Purbalingga community, namely the attitude of the parties to accept and use consensus methods in dispute resolution. The purpose of rembugan is to achieve harmony and togetherness. The mediator is the Environment Agency (DLH) and Village Head (Kepala Desa). Strengthening rembugan position in the dispute resolution model is supported by Purbalingga community culture, whose characters are honest, free, open, egalitarian, and accepting of consensus.  Strengthening rembugan as a mediation model is also supported by government institutions such as village heads and Environment Agency, and is formally regulated in Law No. 32 of 2009 concerning environmental protection and management.